The effect of age on language attrition: Evidence from bilingual returnees - Flores, Cristina (2010)
The present study investigates the syntactic competence of bilingual Portuguese-German returnees who have lost regular contact with their L2 (German). The main criterion which distinguishes the participants is the age of input loss. This allows their division into two main groups: speakers who lost German input during early childhood (between ages seven and ten) and speakers who were eleven or older when they moved away from the German environment. Focusing on verb placement in main and embedded clauses, the available data show strong evidence of the existence of a stabilization phase following the acquisition period. The speakers who lost L2 input earlier than age eleven show significantly more syntactic deficits than the other speakers. However, the observed attrition effects seem to be the result of insufficient L2 activation, rather than the expression of undergoing competence loss.